2015
DOI: 10.1063/1.4939277
|View full text |Cite
|
Sign up to set email alerts
|

Phonon wave-packet scattering and energy dissipation dynamics in carbon nanotube oscillators

Abstract: Friction in carbon nanotube (CNT) oscillators can be explained in terms of the interplay between low frequency mechanical motions and high frequency vibrational modes of the sliding surfaces. We analyze single mode phonon wave packet dynamics of CNT based mechanical oscillators, with cores either stationary or sliding with moderate velocities, and study how various individual phonons travel through the outer CNT, interact with the inner nanostructure, and undergo scattering. Two acoustic modes (longitudinal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…LA phonons display significant scattering (down to ∼0.5) in this range. The profile of the dip in the transmission plot at low energy range (5–15 meV) is the characteristic of the inner core geometry and, as suggested in our earlier work, can serve as an identifying signature of the core.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…LA phonons display significant scattering (down to ∼0.5) in this range. The profile of the dip in the transmission plot at low energy range (5–15 meV) is the characteristic of the inner core geometry and, as suggested in our earlier work, can serve as an identifying signature of the core.…”
supporting
confidence: 70%
“…We found the radial breathing and twisting acoustic modes with high group velocity, which exhibit no coupling at the interface, as the enablers of ultralow friction in CNT oscillators. On the other hand, longitudinal acoustic (LA), transverse acoustic, and first-oder optical modes are chiefly responsible for dissipation in CNT oscillators by causing substantial scattering in the 5–15 meV range . LA phonons have recently been found to enhance the flow of confined water in multiwalled CNTs by causing an oscillatory shear stress at the interface …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wave packets of BR and TW modes transfer almost no energy in to the inner core and show a consistent ideal transmission throughout the frequency range. 31 TA and FO modes showed a significant scattering in the low energy region however the mechanism of scattering is distinct from that of LA mode. Unlike LA phonon, the mode characteristic of TA and FO phonons involve dominant transverse component of atomic displacements and hence no net axial force on the end atoms of the core.…”
mentioning
confidence: 83%
“…Along with LA mode, we studied two other acoustic modes (TA and TW) and two optic modes (BR and FO) and found that the scattering mechanism showed by the LA mode (Figure and Figure ) only can initially generate a net axial force on core. The wave packets of BR and TW modes transfer almost no energy in to the inner core and show a consistent ideal transmission throughout the frequency range . TA and FO modes showed a significant scattering in the low energy region however the mechanism of scattering is distinct from that of LA mode.…”
Section: Scattering Of Single Mode Phonon Wave Packetsmentioning
confidence: 94%